Analisis Portofolio Ekonomi Kota Tarakan - Margiyono, Margiyono (Ekonomika, 2010)
The purpose of this study are : (1) Identify sectoral economic potential and economic competitiveness in Tarakan City; (2) To identify the description of the economy and economic potential, through the analysi of the economic portofolio, (3) To formulate a model of economic development and sector development strategies, in Tarakan City economy sector; (4) Designing the utilization of the potential of each sector in order to encourages economic growth and increasing income Tarakan City community. Analysis tool used is Location Quotient Analysis, Analysis Of Multiplier and Economic Sector Categorization.Key Words: Potential Economic, Economic Sector, Competitiveness